N‐acylethanolamine‐hydrolysing acid amidase: A new potential target to treat paclitaxel‐induced neuropathy. (23rd March 2021) - Toma, Wisam; Caillaud, Martial; Patel, Nipa H.; Tran, Tammy H.; Donvito, Giulia; Roberts, Jane; Bagdas, Deniz; Jackson, Asti; Lichtman, Aron; Gewirtz, David A.; Makriyannis, Alexandros; Malamas, Michael S.; et al.
Abstract: Background: Although paclitaxel is an effective chemotherapeutic agent used to treat multiple types of cancer (e.g. breast, ovarian, neck and lung), it also elicits paclitaxel‐induced peripheral neuropathy (PIPN), which represents a major dose‐limiting side effect of this drug. Methods: As the endogenously produced N ‐acylethanolamine, palmitoylethanolamide (PEA), reverses paclitaxel‐induced mechanical hypersensitivity in mice, the main goals of this study were to examine if paclitaxel affects levels of endogenous PEA in the spinal cord of mice and whether exogenous administration of PEA provides protection from the occurrence of paclitaxel‐induced mechanical hypersensitivity. We further examined whether inhibition of N‐acylethanolamine‐hydrolysing acid amidase (NAAA), a hydrolytic PEA enzyme, would offer protection in mouse model of PIPN. Results: Paclitaxel reduced PEA levels in the spinal cord, suggesting that dysregulation of this lipid signalling system may contribute to PIPN. Consistent with this idea, repeated administration of PEA partially prevented the paclitaxel‐induced mechanical hypersensitivity. We next evaluated whether the selective NAAA inhibitor, AM9053, would prevent paclitaxel‐induced mechanical hypersensitivity in mice. Acute administration of AM9053 dose‐dependently reversed mechanical hypersensitivity through a PPAR‐α mechanism, whereas repeated administration of AM9053 fully prevented the development of PIPN, without any evidence of tolerance. Moreover, AM9053 produced a conditioned place preference in paclitaxel‐treated mice, but not in control mice. This pattern of findings suggests a lack of intrinsic rewarding effects, but a reduction in the pain aversiveness induced by paclitaxel. Finally, AM9053 did not alter paclitaxel‐induced cytotoxicity in lung tumour cells. Conclusions: Collectively, these studies suggest that NAAA represents a promising target to treat and prevent PIPN. Significance: The present study demonstrates that the chemotherapeutic paclitaxel alters PEA levels in the spinal cord, whereas repeated exogenous PEA administration moderately alleviates PIPN in mice. Additionally, targeting NAAA, PEA's hydrolysing enzyme with a selective compound AM9053 reverses and prevents the PIPN via the PPAR‐α mechanism. Overall, the data suggest that selective NAAA inhibitors denote promising future therapeutics to mitigate and prevent PIPN. Abstract :